Descriptive Study of Leadership Succession Process at UD. Sukses - Darmawan, Yulius (Agora, 2014)
In a family business is certainly clear that the desire of the founders would want to have a successor who will replace the family business. An interesting thing that many surviving family company and it is certainly stems from a family company that successfully execute on the companys leadership succession. Therefore, this study aims to determine the leadership succession process conducted at UD. Sukses. Collecting data in this study using the interview method. In determining the informant, the authors used a purposive sampling method. To test the validity of the data, using triangulation by comparing the results of inter-informant interviews and supported by documentation of the results of the photographs. At this stage of the business pre incumbent assign tasks entrusted to the successor to run and get the feel of doing business successor. At this stage of education and personal development, the successor to follow any formal education until high school, and the other successor gain knowledge of learning directly from the incumbent. At the stage of proof of competence, motivation and work experience, the successor has a great curiosity to address and resolve existing responsibilities, for work experience, where the successor has experience since junior successor already helped the incumbent at UD. Sukses. At this stage of the formal start of business, the successor to the business through a commitment to providing the best because it is a life choice. In the declaration phase of succession, UD. Sukses does not yet have a plan for submission toward full office of the incumbent to the successor and to date the activities that took place more as a partner working and learning from the father to his son.